Countdown to a new library managing the building project - Woodward, Jeannette A. (Chicago American Library Association, 2010)
Writing from the perspective of a librarian who has been through numerous building projects, Jeannette Woodward walks you through the process of overseeing the planning and construction of a building project. Packed with helpful checklists and worksheets, this revised edition includes: updated references, standards, materials, and resources; tips for efficient HVAC systems and evolving rules for LEED certification; and, information on new technological issues. Using hands-on tools and real-life insider stories from librarians around the country, this is a must-have crash course in planning and building today's libraries.
Off to a good start -- The world of architects and contractors -- The emerging library design -- Functional and sustainable buildings -- Human needs and energy-efficient buildings -- Technology in twenty-first-century buildings -- Security and safety in today's world -- Creating customer-friendly spaces : it's not just decor -- Surviving construction -- Moving in and getting settled.
Electronic reproduction.
Keywords: Library buildings -- United States -- Design and construction; Electronic books